Integration of Mathematics with other Sciences (Texas Journal of Multidisciplinary Studies, 2022)
This article is written about the integral relationship of mathematics with other disciplines and the importance of an integrative approach in the effective organization of lessons in this discipline. The interrelationships of mathematics and physics, the educational and methodological significance of integrative approaches were also discussed.